The use of carboxymethylcellulose gel to increase non-viral gene transfer in mouse airways. - Griesenbach, U; Meng, C; Farley, R; Wasowicz, M; Munkonge, F; Chan, M; Stoneham, C; Sumner-Jones, S; Pringle, I; Gill, DR; Hyde, S; Stevenson, B; et al. (2010)
We have assessed whether viscoelastic gels known to inhibit mucociliary clearance can increase lipid-mediated gene transfer. Methylcellulose or carboxymethylcellulose (0.25-1.5%) was mixed with complexes of the cationic lipid GL67A and plasmids encoding luciferase and perfused onto the nasal epithelium of mice. Survival after perfusion with 1% CMC or 1% MC was 90 and 100%, respectively. In contrast 1.5% CMC was uniformly lethal likely due to the viscous solution blocking the airways. Perfusion with 0.5% CMC containing lipid/DNA complexes reproducibly increased gene expression by approximately 3-fold (n=16, p<0.05). Given this benefit, likely related to increased duration of contact, we also assessed the effect of prolonging contact time of the liposome/DNA complexes by delivering our standard 80 microg DNA dose over either approximately 22 or 60 min of perfusion. This independently increased gene transfer by 6-fold (n=8, p<0.05) and could be further enhanced by the addition of 0.5% CMC, leading to an overall 25-fold enhancement (n=8, p<0.001) in gene expression. As a result of these interventions CFTR transgene mRNA transgene levels were increased several logs above background. Interestingly, this did not lead to correction of the ion transport defects in the nasal epithelium of cystic fibrosis mice nor for immunohistochemical quantification of CFTR expression. To assess if 0.5% CMC also increased gene transfer in the mouse lung, we used whole body nebulisation chambers. CMC was nebulised for 1h immediately before, or simultaneously with GL67A/pCIKLux. The former did not increase gene transfer, whereas co-administration significantly increased gene transfer by 4-fold (p<0.0001, n=18). This study suggests that contact time of non-viral gene transfer agents is a key factor for gene delivery, and suggests two methods which may be translatable for use in man.